The Influence of Academic Supervision and Principal’s Leadership Style on Learning Quality - Rizka Septalia; Rohana Rohana; Reva Maria Valianti (Journal of Social Work and Science Education, 2026)
This study aims to analyze the influence of academic supervision and the principal’s leadership style on learning quality in State Junior High Schools within Tebing Tinggi District, examining both partial and simultaneous effects. Employing a quantitative ex post facto method, data were collected via questionnaires and documentation from a sample of 101 teachers and analyzed using SPSS. The results confirm that both academic supervision and leadership style individually have a significant positive influence on learning quality. Furthermore, their combined effect is substantially greater, demonstrating a synergistic relationship. The novelty of this research lies in its integrated examination of these two managerial functions within a specific Indonesian district context, highlighting their interdependence in driving instructional improvement. A key practical implication is the necessity for district-level professional development programs that train principals to integrate formative academic supervision with supportive, transformational leadership practices. This study contributes to the field of educational leadership by providing empirical evidence that learning quality is best enhanced through a dual-strategy approach, simultaneously strengthening pedagogical oversight and fostering a positive, directive school climate.